Recording, analysis, and interpretation of the hull remains of Santo Hieronimo (1576), a vessel from the merchant fleet of the Maritime Republic of Ragusa - Casabán, Jose L. (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Following the discovery of the remains of Santo Hieronimo in the early 1970s near the Island of Šipan (Croatia), the Maritime Museum of Dubrovnik carried out the rescue excavation of the wreck. The pioneering work led to the preliminary interpretation of hull remains and recovered artifacts. Ten years later, the research conducted at the National Archive of Dubrovnik resulted in the identification of the sunken ship. The archaeological study of the remains of Santo Hieronimo continued in 2014. This paper presents the latest research results on the hull features of Santo Hieronimo, aimed at understanding the shipbuilding techniques of the post-medieval vessels that sailed the Adriatic.